Role of Peer Attitudes in Shaping Employee Productivity of Non-Teaching Staff in a Government Agency Division in the Philippines - April R Evangelista; Jesus P Briones; Flormando P Baldovino; Rey Fernan G Refozar (Research Synergy Foundation, 2025)
Peer attitudes can exert a powerful influence on individuals, both directly and indirectly, shaping their behaviors, beliefs, and even their personal development. This study determined the impact of peer attitudes on the productivity of non-teaching staff in a division office of a government agency in the Philippines. Employing a descriptive-quantitative design, the study assessed the role of peer attitudes in shaping the non-teaching staff’s employee productivity. Data were collected from 65 government agency employees using a researcher-structured questionnaire prepared through Google form and distributed via Facebook Messenger and personal emails. Statistical tests included frequency count, percentage, weighted mean, and the Spearman Rank Correlation technique to quantify the strength and direction of the relationship between PAT and employee productivity. The findings highlighted the vital role of positive peer interactions in boosting employee productivity and cultivating a collaborative work environment. Although negative behaviors are infrequent, addressing disruptive attitudes to ensure a workplace where positive interactions flourish and a strong organizational identity thrive is essential. While challenges related to peer attitude rarely occur in the agency, the researchers suggest a roadmap for molding staff employee productivity. This study can serve as baseline information for developing studies on the effects of peer attitudes toward employee productivity and fostering a healthier workplace culture among government educational institutions.